2020
DOI: 10.7717/peerj.8470
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis and transcription factors responsive to drought stress in Hibiscus cannabinus

Abstract: Kenaf is an annual bast fiber crop. Drought stress influences the growth of kenaf stems and causes a marked decrease in fiber yield and quality. Research on the drought resistance of kenaf is therefore important, but limited information is available on the response mechanism of kenaf to drought stress. In this study, a transcriptome analysis of genes associated with the drought stress response in kenaf was performed. About 264,244,210 bp high-quality reads were obtained after strict quality inspection and data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Proteomics, which is the study of the structural and functional features of all the proteins in an organism, is an important means of understanding complex biological mechanisms, including plant responses to abiotic stress tolerance (Deshmukh et al, 2014). Using transcriptomic or proteomics sequencing, many genes associated with drought response were identified in a number of plants, such as Arabidopsis (Cho et al, 2013; Matsui et al, 2008; Meng et al, 2019), rice (Hamzelou et al, 2020; Li et al, 2019), wheat (Fotovat et al, 2017; Kang et al, 2012; Ma et al, 2017; Michaletti et al, 2018), maize (Zeng et al, 2019; Zheng et al, 2020), soybean (Song, Prince, et al, 2016; Wang & Komatsu, 2018), tobacco (Chen et al, 2019; Khan et al, 2019), and others (An et al, 2020; Ghatak et al, 2017; Jangpromma et al, 2010; Ngara & Ndimba, 2013; Raney et al, 2014; Rodziewicz et al, 2019; Singh et al, 2017; Utsumi et al, 2012; Wisniewski et al, 2009; Yang et al, 2017). In rapeseed, numerous candidate genes associated with drought response have also been identified by transcriptomic and proteomics analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics, which is the study of the structural and functional features of all the proteins in an organism, is an important means of understanding complex biological mechanisms, including plant responses to abiotic stress tolerance (Deshmukh et al, 2014). Using transcriptomic or proteomics sequencing, many genes associated with drought response were identified in a number of plants, such as Arabidopsis (Cho et al, 2013; Matsui et al, 2008; Meng et al, 2019), rice (Hamzelou et al, 2020; Li et al, 2019), wheat (Fotovat et al, 2017; Kang et al, 2012; Ma et al, 2017; Michaletti et al, 2018), maize (Zeng et al, 2019; Zheng et al, 2020), soybean (Song, Prince, et al, 2016; Wang & Komatsu, 2018), tobacco (Chen et al, 2019; Khan et al, 2019), and others (An et al, 2020; Ghatak et al, 2017; Jangpromma et al, 2010; Ngara & Ndimba, 2013; Raney et al, 2014; Rodziewicz et al, 2019; Singh et al, 2017; Utsumi et al, 2012; Wisniewski et al, 2009; Yang et al, 2017). In rapeseed, numerous candidate genes associated with drought response have also been identified by transcriptomic and proteomics analyses.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lignin was recognized as having an important role in drought resistance [ 66 ] while the CAD enzyme was used to characterize drought tolerance [ 67 ]. Here, the phenylpropanoid biosynthesis (ko00940), as a stress-resistant pathway [ 68 ], was enriched in the KEGG analysis, while the contents of lignin and CAD activities were significantly changed ( Figure 9 ). In addition, the three pathways have been reported to participate in responding to abiotic stress in Hibiscus cannabinus , Miscanthus and tomato ( Solanum lycopersicum ) [ 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kenaf has a high yield of biomass and is widely used, including papermaking, ropes, textiles, animal feed, compounding agents, construction and ltration materials, and can also be used for board making and as a source of biomass energy (Li et al 2021b;Tang et al 2019). Based on the characteristics of strong resistance, such as saline (Wei et al 2019), drought (An et al 2020b) and heavy metal (Chen et al 2021b), it is also considered as a good candidate for bioremediation. To uncover the molecular mechanism involved in salt tolerance in kenaf, our previous proteomic study has revealed several key regulatory pathways and identi ed a lot of proteins associated with salt-stress tolerance (Kashif et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…To uncover the molecular mechanism involved in salt tolerance in kenaf, our previous proteomic study has revealed several key regulatory pathways and identi ed a lot of proteins associated with salt-stress tolerance (Kashif et al 2020b). In addition, a lot of transcription factors have been characterized to be-associated with drought stress response by transcriptome analysis (An et al 2020b). However, the salt and drought resistance mechanism of kenaf still needs further study.…”
Section: Introductionmentioning
confidence: 99%